1990
DOI: 10.1007/bf00903788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of microbial surfactants on hydrocarbon degradation in a soil population in a stirred reactor

Abstract: The hydrocarbon degradation rate could be doubled by the addition of sophorose lipids as biosurfactants in a model system containing 10% soil and a 1.35% hydrocarbon mixture of tetradecane, pentadecane, hexadecene, 1,2,4-trimethylcyclohexane, pristane (2,6,10,14-tetramethylpentadecane) phenyldecane and naphthalene suspended in mineral salts medium. The adaptation phases for two degradation phases were shortened, and the extent of degradation and final biomass were increased. The added biosurfactants were degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(89 citation statements)
references
References 7 publications
0
87
0
2
Order By: Relevance
“…Hydrocarbon contaminants may be nonavailable because of their hydrophobic nature and sorption to soil. Oberbremer et al (34) showed that both the rate and extent of hydrocarbon degradation in soil slurry were enhanced by biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrocarbon contaminants may be nonavailable because of their hydrophobic nature and sorption to soil. Oberbremer et al (34) showed that both the rate and extent of hydrocarbon degradation in soil slurry were enhanced by biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that hydrocarbon internalisation is mediated by the formation of microemulsion, presumably by lowering interfacial tension 59 . Although, literature on the effect of surfactant on oil utilisation ability shows varying results, majority of reports indicate its important role in effective dispersion and degradation of pollutant oil in marine environment [60][61][62][63] .…”
Section: Bioremediation: Why ? and How ?mentioning
confidence: 99%
“…Microbes produce surface-active agents,biosurfactants, when grown on insoluble or immiscible compounds (Desai and Banat, 1997;Lin, 1996;Neu, 1996). The use of biosurfactants has been proposed as an alternative to chemical surfactants to enhance the bioavailability of hydrophobic contaminants (Hunt et al, 1994;Oberbremer et al, 1990). Biosurfactants are a structurally diverse group of surface-active agents.…”
Section: Microbiological Studiesmentioning
confidence: 99%